Haptic Issues for Virtual Manipulation - Hinckley, Ken (University of Virginia, 1996)
The Windows-Icons-Menus-Pointer (WIMP) interface paradigm dominates modern computing systems. Yet these interaction techniques were originally developed for machines that are now 10, 15, or nearly 20 years old. Human-computer interaction currently faces the challenge of getting past this “WIMP plateau” and introducing new techniques which take advantage of the capabilities of today’s computing systems and which more effectively match human capabilities. Two-handed spatial interaction techniques form one possible candidate for the post-WIMP interface in application areas such as scientific visualization, computer aided design, and medical applications. The literature offers many examples of point design, offering only a description of the thing (what the artifact is) and not the process. But point design only provides a hit-ormiss coverage of the design space and does not tie the multiplicity of efforts into a common understanding of fundamental issues. To get past the WIMP plateau, we need to understand the nature of human-computer interaction as well as the underlying human capabilities. My research contributes a working system which has undergone extensive informal usability testing in the context of real domain experts doing real work, and it also presents the results of experimental evaluations which illustrate human behavioral principles. Together, these approaches make a decisive statement that using both hands for virtual manipulation can result in improved user productivity. I contribute to the field by: Showing that virtual manipulation needs to study the feel of the interface, and not just the graphical look of the interface; Applying virtual manipulation technology to a volume visualization application which has been well received by neurosurgeons; Demonstrating two-handed virtual manipulation techniques which take advantage of the highly developed motor skill of both hands; Contributing basic knowledge about how two hands are used; Showing that two hands are not just faster than one hand, but that two hands together provide information which one hand alone cannot, and can change how users think about a task; and finally Providing an overall case study for an interdisciplinary approach to the design and evaluation of new human-computer interaction techniques.